2012
DOI: 10.1002/adma.201200810
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Interconnected Microchannel Network Formed in Gelatin by Sacrificial Shellac Microfibers

Abstract: 3D microfluidic networks are fabricated in a gelatin hydrogel using sacrificial melt-spun microfibers made from a material with pH-dependent solubility. The fibers, after being embedded within the gel, can be removed by changing the gel pH to induce dissolution. This process is performed in an entirely aqueous environment, avoiding extreme temperatures, low pressures, and toxic organic solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
85
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 33 publications
1
85
0
Order By: Relevance
“…Additional studies have confirmed the significance of mural cells in stimulating basement membrane assembly that contributes to the stability of the endothelial lining. 14,17,21,[26][27][28][29] Without smooth muscle cell support, endothelial cells are susceptible to detachment and apoptosis, a finding that is confirmed in our HUVEC-only-seeded microchannels. vWF and CD31 expression are two of the most widely cited markers of endothelial cell function in vitro 28 ; both were widely expressed within the neointima of our seeded microchannels.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Additional studies have confirmed the significance of mural cells in stimulating basement membrane assembly that contributes to the stability of the endothelial lining. 14,17,21,[26][27][28][29] Without smooth muscle cell support, endothelial cells are susceptible to detachment and apoptosis, a finding that is confirmed in our HUVEC-only-seeded microchannels. vWF and CD31 expression are two of the most widely cited markers of endothelial cell function in vitro 28 ; both were widely expressed within the neointima of our seeded microchannels.…”
Section: Discussionsupporting
confidence: 57%
“…A number of polymers including sucrose, 19 carbohydrate glass 20 (a combination of glucose, sucrose, and dextran), shellac, 21 and alginate 22 have been utilized as sacrificial microfibers to create vascular networks within a bulk polymer. In previous work, we employed a sacrificial microfiber technique whereby three-dimensional (3D) vascular networks were cast within a polydimethylsiloxane (PDMS) bulk using sacrificial melt-spun sucrose with 1 mm sucrose inlet and outlet sticks, forming the hierarchal architecture of a capillary bed, feeding artery, and draining vein respectively.…”
mentioning
confidence: 99%
“…[12][13][14][15][16][17][18] Methods of microvascular fabrication, such as the vaporization of a sacrificial component (VaSC), lithographic techniques, direct-write approaches, and many others, can form these micrometer-sized features. [19][20][21][22][23][24][25][26][27] At the micrometer scale, differences from the macroscale arise, as surface tension counteracts gravitational effects and laminar rather than turbulent flows are dominant. [28] The mechanisms of two-phase heat transfer and its relationship to gas nucleation is not yet fully understood, as the methods of characterizing these systems can vary widely.…”
mentioning
confidence: 99%
“…[14][15][16] Tissue engineering scaffolds with pre-fabricated microvascular networks can dramatically reduce the characteristic length scale for diffusion in bulk materials. [17][18][19][20][21] Vascularized scaffolds can accelerate nutrient supply and waste removal in highly metabolically active tissues such as the liver, heart, and kidney. [22][23][24] The maximum thickness of engineered tissue in the smallest dimension is ultimately limited by oxygen diffusion and is typically on the order of 150 μ m. [ 25 ] Integrating vascular networks into scaffolds may permit an increase in the total volume of tissue constructs while maintaining a constant effective macroscopic diffusion length scale that permits adequate supply of nutrients.…”
Section: Introductionmentioning
confidence: 99%